Curriculum leadership - Glatthorn, Allan A.,|d 1924- (Sage, 2007)
"A one-of-a-kind resource written for educational leaders-teachers and administrators-who want to successfully restructure and enhance school curriculum"Praise for the First Edition""Curriculum Leadership presents the fundamentals of the curriculum development process and provides educators with the foundation to be curriculum specialists."-"Amany Saleh, " Arkansas State University" ""Curriculum Leadership provides tried and true techniques that teachers can use right away, right now, to make writing curriculum a rewarding experience that benefits the curriculum writer and the teachers who will be asked to implement the curriculum."-"Clyde Winters, " Governors State University"\Curriculum Leadership: Strategies for Development and Implementation, Second Edition is a much-needed, highly informative, and easy-to-read account of curriculum development and implementation for those aspiring to become curriculum decision makers. This important book-which helps bridge curriculum's rich historical past to today's global education world-is essential for educational leaders in the planning, alignment, and development of curriculum to meet state, national, and international standards. Authors Allan A. Glatthorn, Floyd Boschee, and Bruce M. Whitehead provide innovative and successful curriculum ideas that include reflective case studies with challenges and key issues/questions, Key to Leadership sections, curriculum tips, an Applications section, and a Webliography in every chapter. Also interspersed throughout the book are tried-and-true strategies that provide administrators with innovative ideas on meeting state and national standards. New to this edition Coverage of multicultural and global education Integration of NCATE and standards coverageNew technology strategies, including added emphasis on e-learning.\High-quality ancillaries Available to qualified instructors upon request, Instructors' Resources on CD-ROM include PowerPoint lecture slides, a comprehensive test bank, sample syllabi, and more. Intended AudienceThis is a much needed, highly informative, and easy-to-read account of curriculum development and change for curriculum leaders, those teaching curriculum courses, and those aspiring to become curriculum decision makers. It provides the knowledge and skills needed to develop and implement a K-12 school curriculum.